Color confinement and dual superconductivity of the vacuum. II - Biagio Lucini (Physical Review D, 1999)
The dual superconductivity of the vacuum in SU(3) gauge theory is investigated by constructing a disorder parameter which signals monopole condensation in various abelian projections and by studying numerically on the lattice its behaviour at finite temperature. We find that the vacuum is a dual superconductor with respect to each U(1) of the residual gauge group after abelian projection independently of the abelian projection chosen. Like in the SU(2) case (discussed in a companion paper) a finite size scaling analysis enables us to extract the indices of the phase transition and our analysis is consistent with independent determinations.